Conformationally confined three-armed supramolecular folding for boosting near-infrared biological imaging - Wang, Hui-Juan; Zheng, Meng-Meng; Xing, Wen-Wen; Li, Yong-Xue; Wang, Yao-Yao; Zhu, Hongjie; Zhang, Ying-Ming; Yu, Qilin; Liu, Yu (Chemical science (Cambridge), 2023)
Herein, a triphenylamine derivative ( TP-3PY ) possessing 4-(4-bromophenyl)pyridine (PY) as an electron-accepting group and tris[ p -(4-pyridylvinyl)phenyl]amine (TPA) with large two-photon absorption cross-sections as an electron-donating group was obtained, and showed intense absorption in the visible light region ( λ max = 509 nm) and weak near-infrared (NIR) fluorescence emission at 750 nm. After complexation with cucurbit[8]uril (CB[8]), TP-3PY showed bright NIR fluorescence emission at 727 nm and phosphorescence emission at 800 nm. When the supramolecular assembly ( TP-3PY ⊂CB[8]) further interacted with dodecyl-modified sulfonatocalix[4]arene (SC4AD), the fluorescence and phosphorescence emissions were further enhanced at 710 and 734 nm, respectively. However, only the fluorescence emission of TP-3PY was enhanced in the presence of cucurbit[7]uril (CB[7]) and SC4AD. More interestingly, the photoluminescence of TP-3PY ⊂CB[8]@SC4AD and TP-3PY ⊂CB[7]@SC4AD assemblies could be excited by both visible (510 nm) and NIR light (930 nm). Finally, these ternary supramolecular assemblies with bright NIR light emission were applied to lysosome imaging of tumor cells and real-time biological imaging of mice. A conformation confined NIR photoluminescent supramolecular foldamer was constructed and used for lysosome-targeted imaging and real-time in vivo imaging of intact animals.